PROFESSIONAL SERVICES AND TOOLS FOR THE TRAINING OF THE FUTURE ECONOMICS: EXPERT OPINION - Glazunova, Olena; Saiapina , Taisiia; Korolchuk, Valentyna (Physical and Mathematical Education, 2022)
Formulation of the problem. The use of digital technologies transforms the branches of the economy and the processes of interaction between the participants of economic activity, therefore the formation and development of digital competencies of the future economists, both general and professional, is one of the main tasks of modern institutions of higher education in training such specialists and improving their qualifications, which meets the modern requirements of the labor market.Materials and methods. In order to solve the problem, the analysis, classification, and systematization of scientific sources were carried out, and the method of expert evaluation to conduct an expert evaluation of professional services and tools that are the most effective in training future economists was used.The results. The article summarizes the results of a pedagogical study with the participation of 20 student-experts who studied in the specialty 051 "Economics" of the educational program "Economics of Enterprise" of the NULES of Ukraine. The categories of professional services and tools for the training of the future specialists were defined, the selection of professional services and tools for each component of the digital competence was carried out and their expert evaluation was carried out accordingly.Conclusions. The results of the research made it possible to select professional tools and services that should be used for the formation of each of the components of digital competence, namely: "Digital identity", "Digital use", "Digital risks", "Digital security", "Digital emotional intelligence", "Digital Communication", "Digital Literacy" and "Digital Rights" as part of studying the discipline Information Systems and Technologies in the Economy. The dedicated services and tools for the formation of digital competence of future economists covered a wide range of professional tools for the organization of various types of educational activities for students.
Keywords: professional services; professional tools; training of future economists; formation of digital competence